Psychiatric Genetics in the post genome age - CORVIN, AIDEN; GILL, MICHAEL (The Royal College of Psychiatrists, 2003)
Less than 50 years after publication of the structure of DNA, we possess a working draft of the human genome and expect a completed draft listing all genes and their location by 2003 (International Human Genome Sequencing Consortium, 2001). For 21st-century medicine, the genome will offer a gateway to new biological mechanisms that integrate our genetic and environmental understanding of behaviour and disease. In psychiatry a genetic contribution to common disorders, cognition and personality traits is well established, and susceptibility loci have been identified for schizophrenia, bipolar affective disorder, autism and Alzheimer's disease.
PUBLISHED
Keywords: Psychiatry